2008
DOI: 10.1007/s11250-008-9250-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic parameters and annual trends for growth and fertility traits of Charolais and Hereford beef cattle breeds in Kenya

Abstract: This study estimated genetic and phenotypic parameters and annual trends for growth and fertility traits of Charolais and Hereford cattle in Kenya. Traits considered were birth weight (BW, kg), pre-weaning average daily gain (ADG, kg/day) and weaning weight (WW, kg); calving interval (CI, days) and age at first calving (AFC, days). Direct heritability estimates for growth traits were 0.36 and 0.21; 0.25 and 0.10; 0.23 and 0.13 for BW, ADG and WW in Charolais and Hereford, respectively. Maternal heritability es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…The heritability estimate for AFC was similar to the estimate of 0.33 reported by Ruiz-Sánchez et al (2007) in high environment US Holsteins and was lower than the estimate of 0.38 by Ojango and Pollott (2001). However, Orenge et al (2009) found the heritability estimate of 0.16 for Holsteins, but the heritability estimate for PPER was similar to the report of these researchers. Heritability estimates of milk yield and constituents described in this study were generally lower than those reported in the literature (e.g.…”
Section: Discussionsupporting
confidence: 79%
“…The heritability estimate for AFC was similar to the estimate of 0.33 reported by Ruiz-Sánchez et al (2007) in high environment US Holsteins and was lower than the estimate of 0.38 by Ojango and Pollott (2001). However, Orenge et al (2009) found the heritability estimate of 0.16 for Holsteins, but the heritability estimate for PPER was similar to the report of these researchers. Heritability estimates of milk yield and constituents described in this study were generally lower than those reported in the literature (e.g.…”
Section: Discussionsupporting
confidence: 79%
“…Khan et al 1999;Maiwashe et al 2002;Wasike et al 2009). However, positive correlations of 0.47 and 1.00 for BW were reported for Zebu crossbreds in Ethiopia (Demeke et al 2003) and Hereford calves in Kenya (Orenge et al 2009), respectively. The correlation estimated for WW (−0.65) in this study is lower than the estimate of −0.25 reported by Wasike et al (2009) Maiwashe et al (2002) reported an estimate of −0.54 for WW in Bonsmara cattle in South Africa.…”
Section: Resultsmentioning
confidence: 97%
“…In a study on Boran cattle in Kenya, Wasike et al (2009) reported low maternal environmental variance at birth (c 2 =0.16); however, unlike in our study and those mentioned, maternal environmental effects played a great role accounting for a significant variation in pre-weaning growth. The relatively large phenotypic variances for pre-weaning growth performance in tropical cattle breeds under the cow-calf feeding system is a reflection of differences in individual dam's milk production and mothering ability (Orenge et al 2009;Wasike et al 2009), compared to artificial feeding systems where calves are subjected to relatively uniform feeding regimes (e.g. Khan et al 1999;Demeke et al 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations